How we talk(ed) about it: Ways of speaking about computational architecture. (June 2022) - Horvath, Anca-Simona
If we understand architecture as a three-part system formed by the building, its image, or drawings and images describing buildings, and the critical discourse around architecture, then the texts or ways of speaking about architecture play a key role in understanding the field and its development. By analysing a corpus of around 4.6 million words from texts written between 2005 and 2020 that form a part of critical discourse in computational architecture (understood as the result of the intense digitalization of the field), this paper aims to map ways of speaking about computational architecture. This contributes to architectural theory and might help gain a better understanding of the evolution of the digitalization of construction in general. Findings show that computational architecture is surrounded by a specific way of speaking, hybridized with words from fields such as biology, neuroscience, arts and humanities, and engineering. While some topics such as 'sustainability' or 'biology' come up consistently in the discourse, others, such as 'people' or 'human', have periods when they are more and less popular. After highlighting open research questions, the paper concludes by presenting a map of periodic and recurring topics in ways of speaking about computational architecture over the last 15 years, thus tracking and documenting long-term trends, and illuminating patterns in the broader field of digital construction.